Thermal Stability of Nanocrystalline NiS2 as High Specific Capacity Thermal Battery Cathode Material. Issue 12 (26th July 2020) - Yang, Wenju; Zhou, Lingping; Luo, Zeshunji; Zhu, Jiajun; Yang, Wulin; Li, Deyi; Fu, Licai
Abstract : Nanocrystallization can shorten the Li + transport distance, resulting in the enhancement of electrochemical activity for cathode materials. However, nanocathode materials tend to be thermally unstable, further leading to poor electrochemical performance of a battery system. This disadvantage can be especially detrimental for thermal batteries because they are often operated at high temperatures (≥450 °C). Herein, the decomposition character of NiS2 at 500 °C is investigated. The decomposition temperatures of NiS2 are found to decrease from 510 to 350 °C with the grain size decreasing to 39 nm, due to the dramatically increased surface energy. The decomposition product is confirmed to be NiS, evidenced by a high‐temperature X‐ray diffractometer. The useful mass of the cathode will reduce once the discharging temperature is higher than 500 °C. Namely, although the small grain size shorthens the Li + transport distance, the discharge performance of the NiS2 cathode may also decrease due to its inferior thermal stability. For the Li‐B/LiF–LiCl–LiBr/NiS2 system, the NiS2 with the grain size of 70 nm shows the highest specific capacity of 831 mAh g −1 under the discharging temperature of 500 °C, with the cut‐off voltage of 0.5 V, compared with other grain sizes from 39 to 112 nm. Abstract : There is a critical grain size where the surface energy of nano‐NiS2 changes drastically. The discharge performance of nano‐NiS2 becomes better first and then worsens, as the grain size decreases. The NiS2 ‐20 h (70 nm) shows the best discharge performance with a specific capacity of 831 mAh g −1 .